PARP inhibitors combined with radiotherapy: are we ready? - Sun, Chen; Chu, Alan; Song, Rui; Liu, Shijia; Chai, Ting; Wang, Xin; Liu, Zongwen (Frontiers in Pharmacology, 2023)
PARP was an enzyme found in the nucleus of eukaryotic cells that played a crucial role in repairing damaged DNA. Recently, PARP inhibitors have demonstrated great potential in cancer treatment. Thus, the FDA has approved several small-molecule PARP inhibitors for cancer maintenance therapy. The combination of PARP inhibitors and radiotherapy relies on synthetic lethality, taking advantage of the flaws in DNA repair pathways to target cancer cells specifically. Studies conducted prior to clinical trials have suggested that the combination of PARP inhibitors and radiotherapy can enhance the sensitivity of cancer cells to radiation, intensify DNA damage, and trigger cell death. Combining radiotherapy with PARP inhibitors in clinical trials has enhanced the response rate and progression-free survival of diverse cancer patients. The theoretical foundation of PARP inhibitors combined with radiotherapy is explained in detail in this article, and the latest advances in preclinical and clinical research on these inhibitors for tumor radiotherapy are summarized. The problems in the current field are recognized in our research and potential therapeutic applications for tumors are suggested. Nevertheless, certain obstacles need to be tackled when implementing PARP inhibitors and radiotherapies in clinical settings. Factors to consider when using the combination therapy are the most suitable schedule and amount of medication, identifying advantageous candidates, and the probable adverse effects linked with the combination. The combination of radiotherapy and PARP inhibitors can greatly enhance the effectiveness of cancer treatment.